Perbandingan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Kelas XI yang Dibelajarkan dengan Menggunakan Model Pembelajaran Berbasis Masalah dan Pembelajaran Langsung - Siti Indriyati Idris; Sudding Sudding; Sugiarti Sugiarti (Program Pasca Sarjana UNM, 2020)
The study is experiment research (quasi experiment), which aims at analyzing the differences of critical thinking skill and learning outcomes taught by utilizing Problem-Based Learning and direct learning. The research design employed non-equivalent pretest-posttest control group design. The results of descrective analysis obtained the mean score of critical thinking skill and learning outcomes in experiment class 1 is 77.60, and experiment class 2, 75.36 with each standard of deviation 6.92 and 9.06. The mean percentage of critical thinking skill indicator in experiment class 1 is 83.14 and in experiment class 2 is 78.01. The mean score of learning outcomes taught by utilizing PBM model is higher than the direct learning model. The result of hypothesis test with t=test at the significant level α = 0.05 obtained significance (0.001 < 0.05), indicate that the hypothesis is accepted. The conclusion of the study is there ia a difference of critical thinking skill and learning outcomes of grade XI MIPA at SMAN 15 Makassar taught by utilizing problem based learning model and direct learning on Hydrocarbon Compounds subject.